The effect of Chronic Care Model-based follow-up on self-efficacy and patient-reported outcomes in COPD patients: a randomized controlled study - Yasemin Sazak; Nermin Olgun (BMC Nursing)
Abstract Aim This study evaluated the effects of Chronic Care Model-based follow-up on self-efficacy and patient-reported outcomes in COPD patients. Methods This study was a randomized controlled trial conducted at the Chest Diseases Outpatient Clinic between January 2022 and July 2022. Four components of the Chronic Care Model were used in the study. Patients in the intervention group were given training, and phone calls were made every two weeks. Short informative messages were sent once a week, and the patients were followed up for three months. No intervention was made in the control group. Results The study was completed with 31 interventions and 30 control patients. The intervention was determined to increase patients’ self-efficacy. There were also positive effects on patient-reported outcomes. Patients’ satisfaction with care was found to be at a high level. It was found that the walking distance of the patients increased. Conclusions Our study revealed that using Chronic Care Model-based follow-up in practice may benefit patients. More studies involving the application of the Chronic Care Model in COPD patients are needed to support our research results. Clinical trial registration Before starting the study, ClinicalTrials.gov was recorded (NCT05029557, Registration Date: August 26, 2021, https://clinicaltrials.gov/ ).